Analysis of Chemistry Laboratory Management at SMA Negeri 2 Percut Sei Tuan - Elisabeth Frenklin Pangaribuan; Nurfajriani; Aulia Hutasuhut; Vesa Veorrela (Jurnal Inovasi Pembelajaran Kimia, 2026)
This study analyzes the management of the chemistry laboratory at SMA Negeri 2 Percut Sei Tuan by integrating aspects of facilities, administration, organization, safety, and waste management. A descriptive qualitative approach was employed using observation, interviews, and documentation to obtain a comprehensive understanding of laboratory practices. The findings indicate that the laboratory has met basic operational standards and is classified as a Type I laboratory based on PERMENPAN No. 3 of 2010. However, several gaps were identified between facility availability and effective management. These include non-functional infrastructure, incomplete administrative records such as the absence of chemical labeling and stock cards, limited safety facilities (e.g., fire extinguishers and eye wash stations), and inadequate waste management practices. The study highlights that laboratory quality is determined not only by physical resources but also by the integration of management systems, safety implementation, and sustainability practices. The main contribution of this research lies in providing a comprehensive framework for evaluating school laboratory management holistically. Practically, the findings suggest the need for digital inventory systems, improved safety facilities, structured waste management, and regular occupational safety training. This study offers important implications for developing effective, safe, and sustainable chemistry laboratory management in secondary education.